Physiological fibrin hydrogel modulates immune cells and molecules and accelerates mouse skin wound healing - Pereira, Rafaela Vaz Sousa; EzEldeen, Mostafa; Ugarte-Berzal, Estefania; Martens, Erik; Malengier-Devlies, Bert; Vandooren, Jennifer; Vranckx, Jan Jeroen; Matthys, Patrick; Opdenakker, Ghislain (Frontiers in Immunology, 2023)
Whereas many attempts of regenerative medicine have been made for wound healing with growth factors and cell therapies, simple immunological studies are lagging behind. We investigated how fibrin hydrogels modulate immune cells and molecules in skin wound healing in mice. Exogenous fibrin at physiological concentrations decreased neutrophil and increased non-classical Ly6Clow monocyte and resolutive macrophage (CD206+ and CX3CR1+) populations, at day 3 after injury. Fibrin hydrogel reduced the expression of pro-inflammatory cytokines and increased IL-10 levels. In line with these findings, gelatinase B/MMP-9 was decreased, whereas gelatinase A/MMP-2 levels remained unaltered. Frequencies of dermal endothelial cells, fibroblasts and keratinocytes were increased and keratinocyte migration was enhanced by fibrin hydrogel. Importantly, physiological fibrin accelerated the healing of skin wounds in contrast to the highly concentrated fibrin sealant Tisseel, which delayed wound repair and possessed a higher fiber density. Collectively, we show that adding a tailored fibrin hydrogel scaffold to a wound bed positively influences the healing process, modulating leukocyte populations and inflammatory responses towards a faster wound repair.